Myeloma-associated systemic amyloidosis masquerading as NASH-associated cirrhosis and diabetic microvascular complications - Pal, Partha (Oxf Med Case Reports, 2015)
Authors describe the case of a 60-year-old diabetic man who presented with jaundice, ascites and significant weight loss over a period of 2 months. Physical examination revealed firm hepatomegaly with ascites. On evaluation, nephropathy, axonal neuropathy, carpal tunnel syndrome and decompensated cryptogenic liver disease with portal hypertension were found fitting with the diagnosis of diabetic nephropathy and neuropathy and nonalcoholic steato-hepatitis-associated cirrhosis, respectively. It was only after tissue diagnosis and serum protein electrophoresis that a definitive diagnosis of myeloma-related amyloidosis was made. This case emphasizes the fact that due to nonspecific initial presentation and multisystem involvement, a high index of suspicion and prompt use of appropriate tests including tissue diagnosis may be required to diagnose amyloid light-chain amyloidosis, which may be a rare presenting feature of myeloma. It should be differentiated from a commoner multisystem disease like diabetes and its complications.